Depressive symptoms during pregnancy and their risk factors – a cross-sectional study - Feduniw, Stepan; Płaza, Olga; Paździor, Dominika; Kosińska-Kaczyńska, Katarzyna; Szymusik, Iwona; Wielgoś, Mirosław (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. It was established that intragestational depression is a common disease, with the estimated average prevalence of 10–25% in all expectant mothers worldwide. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to evaluate the frequency of depressive symptoms in pregnant women in Poland and to identify which factors may be related to a higher risk of depressive symptoms during pregnancy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A prospective cross-sectional study was performed. Depressive symptoms were assessed with the validated Edinburgh Postnatal Depression Scale (EPDS). 346 women were enrolled in the study. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 130 women (37.6%) scored 13 or more points and were considered as presenting with depressive symptoms. Independent risk factors of depressive symptoms during pregnancy including mood disorders diagnosed before the current pregnancy (aOR=2.68, 95%CI 1.37-5.22), mental disorders confirmed in family members (aOR=2.72, 95%CI 1.24-5.98), unhappiness in their current relationship (aOR=4.0, 95%CI 1.77-9.01), lack of support from family members (aOR=2.73, 95%CI 1.51-4.96) increased the risk of DS and good financial status decreased the risk of DS occurrence (aOR=0.45, 95%CI: 0.25-0.80). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Pregnant women commonly report depressive symptoms. The evaluation of relations with the family members, socio-economic status, former depressive symptoms and possible prenatal depression are essential for proper screening of depression in pregnant women.